A vegetação da Serra do Gigante em Itapuranga-GO : mapeamento, classificação e impactos ambientais - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The occupation of the Cerrado has altered its landscapes and increased the complexity of its mosaic as a result of the transformation in land use and land cover. This process has altered the dynamics of environmental processes due to the advances in anthropic activities, mainly through the conversion of native areas. This is a worrisome situation that leads to the need for monitoring or generating data to analyze the evolution and impacts of these activities in the Cerrado. The objective of this study was to carry out a landscape analysis, phytogeographic mapping, integrated analysis using satellite images and in loco collections with measurements of the vegetation structure, analysis of environmental impacts and landscape modifications resulting from visits to the trails that cross the APA (Area of Environmental Preservation) Serra do Gigante, located in the municipality of Itapuranga-GO. The results are composed of three chapters: Chapter 1: Integrated analysis of the landscape in the APA Serra do Gigante in the municipality of Itapuranga-GO. In this chapter we elaborated maps of geology and geomorphology where we noted the formation of two geological units (A and B) and the prevalence of the relief hills and hills. Hypsometry, in which we observed that the APA presents altitude varying from 649 to 971 meters. As for slope, we observed a greater occurrence of the strong undulated relief with a variation of 20 to 45%. Two soil classes were found on the soil map, namely Cambissolo Háplico distrófico (CXbd) and Argissolo Vermelho-Amarelo eutrófico (PVAe), the former presented greater prevalence, reaching 67.33% of the area. The land use and land cover map shows the occurrence of forest formation; savannah formation; grassland formation; and pasture, with forest formation occurring in 50.2% of the study area. Chapter 2: Forest inventory and phytosociology of the APA Serra do Gigante in the municipality of Itapuranga-GO; through the inventory in 11 plots different physiognomic formations were identified, being grouped into two formations: Savanna and Forest. We sampled 162 individuals distributed in 55 species, 45 genera and 25 botanical families, being the families Vochysiaceae and Fabaceae the most abundant, with 31 and 25 individuals each, representing 44.58% of the total sample, being also observed greater richness for the Savanna formation, which had 41 species with a density of 1,477.77 ind.ha-1 while the Forest formation, had a richness of 20 species with density corresponding to 1,450 ind.ha-1. As for the average diameter and height, it was observed that the forest formation presented an average of 11.11 cm in diameter and 4.95 m in height, while for the Savanna the average values were 8.51 cm in diameter and 2.62 m in height. With the presence of homogeneous floristic structure and heterogeneous soils. Chapter 3: Environmental impact of trails in protected areas: a case study of the APA Serra do Gigante in Itapuranga (Goiás), in which it was possible to observe at different points of the trail studied, impacts caused by trampling and the entry of roads for locomotion of local owners, causing problems such as soil compaction, erosion, modification of the landscape giving way to pasture, trails with silting up and exposed roots, and degraded springs. The analyses made here are important, because it allowed a better understanding of the dynamics of the study area, the floristic-structural differences and the distribution of some plant species. The study promoted the perception that the APA Serra do Gigante, despite some fragilities resulting from the anthropization of some areas, still presents itself in a good state of conservation.
Keywords: Análise integrada; Cerrado; Inventário florestal; Paisagem; Unidade de conservação; Integrated analysis; Forest inventory; Landscape; Conservation unit; GEOCIENCIAS::GEOGRAFIA FISICA